2020
DOI: 10.3390/nu12092676
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Capsinoid Intake on Brown Adipose Tissue Vascular Density and Resting Energy Expenditure in Healthy, Middle-Aged Adults: A Randomized, Double-Blind, Placebo-Controlled Study

Abstract: Capsinoids are some of the most promising ingredients to increase energy expenditure (EE) due to brown adipose tissue (BAT) activation. However, there is limited information regarding the effect of prolonged capsinoid ingestion (CI) on BAT activity and resting EE (REE) in healthy, middle-aged, normal to overweight subjects (Subhealthy) with distinct BAT characteristics. We examined the changes in BAT density (BAT-d), using near-infrared time-resolved spectroscopy, and REE/kg induced by daily CI. Forty Subhealt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
(97 reference statements)
0
7
0
Order By: Relevance
“…Higher resting metabolic rate was reported after acute administration of capsaicin in 18 FDG-BAT–positive individuals ( 714 , 715 ). Six-week capsaicin supplementation in healthy individuals increased supraclavicular BAT 18 FDG uptake ( 716 ) and supraclavicular hemoglobin concentration assessed by near-infrared time-resolved spectroscopy ( 716 , 717 ), taken as a surrogate for BAT vascularization and thermogenic activity. In contrast, acute capsaicin administration did not increase BAT 18 FDG uptake even in healthy individuals displaying a cold-induced increase in BAT 18 FDG uptake ( 715 ).…”
Section: Pharmacological Activation Of Brown Adipose Tissuementioning
confidence: 99%
“…Higher resting metabolic rate was reported after acute administration of capsaicin in 18 FDG-BAT–positive individuals ( 714 , 715 ). Six-week capsaicin supplementation in healthy individuals increased supraclavicular BAT 18 FDG uptake ( 716 ) and supraclavicular hemoglobin concentration assessed by near-infrared time-resolved spectroscopy ( 716 , 717 ), taken as a surrogate for BAT vascularization and thermogenic activity. In contrast, acute capsaicin administration did not increase BAT 18 FDG uptake even in healthy individuals displaying a cold-induced increase in BAT 18 FDG uptake ( 715 ).…”
Section: Pharmacological Activation Of Brown Adipose Tissuementioning
confidence: 99%
“…Furthermore, dietary capsaicin induces browning of white adipose tissue by activating TRPV1 channels ( Baskaran et al, 2016 ; El Hadi et al, 2019 ). Prolonged ingestion of capsinoids for 6 weeks increases BAT vascular density and resting energy expenditure in healthy adults ( Fuse et al, 2020 ). Capsaicin and its analog capsinoids, are representative TRPV1 agonists, and as such decrease body fat through the activation and recruitment of BAT, mimicking the effects of cold induced thermogenesis ( Saito, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, we also confirmed a significant correlation between cold-induced thermogenesis, which is an indicator of BAT activity [ 18 ], and [total-Hb]sup. Furthermore, a longitudinal study found that [total-Hb]sup and 18 FDG-PET/CT parameters increased in parallel during chronic intake of thermogenic capsinoids, which are known to increase the mass and activity of BAT, and decreased after cessation of intake [ 40 , 41 ]. Therefore, we believe that [total-Hb]sup can be used to evaluate BAT-d under thermoneutral conditions.…”
Section: Discussionmentioning
confidence: 99%